Donald T. Giles papers - Giles, Donald T., 1898-1983.; Giles, Donald T., 1924- .
Correspondence, notebooks, photographs, and printed matter chiefly documenting Giles's incarceration as a Japanese prisoner-of-war from 1941 to 1945. Notebooks include names, addresses, and autobiographies of fellow U.S. and Allied prisoners at the camp at Zentsuji on the Japanese island of Shikoku and roster of military personnel on Guam where Giles was taken prisoner (1941 December 10) while serving as vice governor and executive officer of the United States Naval Station (Guam). Legislative files contain Giles's testimony (1946) concerning his experiences in Japanese prison camps and the testimony of two other prisoners concerning their mental and physical health two years after their release. Also includes Giles's manuscript memoir, entitled The Reluctant Guest, edited by his son, Donald T. Giles, Jr., and published in 1994 as Captive of the Rising Sun. Wartime correspondents include Donald T. Giles, Jr., and Virginia Basil Giles.
Library of Congress Prints and Photographs Division.
U.S. naval officer; full name Donald Theodore Giles.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and
Forms part of: Naval Historical Foundation collection
Keywords: Giles, Donald T., -- 1924- -- Correspondence; Giles, Virginia Basil -- Correspondence; United States. -- Navy -- Officers; War crimes -- Japan; World War, 1939-1945 -- Medical care; World War, 1939-1945 -- Prisoners and prisons, Japanese; World War, 1939-1945 -- Psychological aspects; World War, 1939-1945 -- Guam; World War, 1939-1945 -- Japan; Shikoku Region (Japan) -- History; Zentsūji-shi (Japan) -- History; United States Naval Station (Guam); Naval officers